2015
DOI: 10.2106/jbjs.o.00169
|View full text |Cite
|
Sign up to set email alerts
|

The Antiquity of the Cam Deformity

Abstract: It appears that the cam deformity was nonexistent among ancient humans and is perhaps predominantly a product of modern-day stresses. Further clinical investigation into behavioral modifications in adolescence is warranted to potentially prevent the development of deformity and impingement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…The authors were unsure whether this represented differences in activity, diet, or other factors. To our knowledge, no other study of ancient populations has reproduced Moats et al's [14] findings in a different cohort. Interestingly, a recent radiologic evaluation of a single specimen by Zurmühle et al [27] found that cam morphology existed as early as 5000 years ago.…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations
“…The authors were unsure whether this represented differences in activity, diet, or other factors. To our knowledge, no other study of ancient populations has reproduced Moats et al's [14] findings in a different cohort. Interestingly, a recent radiologic evaluation of a single specimen by Zurmühle et al [27] found that cam morphology existed as early as 5000 years ago.…”
Section: Introductionmentioning
confidence: 60%
“…This study was designed to address the reported inconsistencies regarding cam morphology in historical populations. Moats et al [14] found no cam morphology in the population from 1000 years ago, while a single specimen studied by Zurmühle et al [27] suggests that it existed as early as 5000 years ago. Given that it is difficult to make conclusions about whether primary cam existed historically based on a single specimen, our purpose was to search for evidence of cam morphology in the Neolithic population from Iran, the medieval population from Poland, and the contemporary Australian aborigine population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies have disagreed as to whether the cam morphology is a product of modern activities or whether it was present in historical or even ancient populations. Some studies have found evidence of cam morphology in ancient and older 20 th century populations [8,15], while another study examining the osteology from an indigenous North American population from approximately 1000 years ago did not find evidence of cam morphology, suggesting it may be a modern phenomenon [10].…”
mentioning
confidence: 99%